The Network Firm as a Political Coalition. Issue 9 (September 2016) - Whitford, Josh; Zirpoli, Francesco
The article uses a qualitative case study of fifteen years in the production network that revolves about Fiat Auto to depict the "network firm" as a political coalition. The analysis touches on Fiat's radical outsourcing of production in the 1990s, a short-lived and ill-fated alliance with General Motors in 2001, a descent to the brink of bankruptcy in 2004, a return to profitability by 2007, and, finally, the acquisition of control of Chrysler in 2009. The article reconstructs James March's classic Carnegie model of the firm in light of the blurring of organizational boundaries. By marrying that model with ideas drawn from the literatures on organizational networks, social movements, and organizational politics, the article demonstrates that strategic decision-making at Fiat and at key suppliers shaped, and was shaped by, an interplay of frames and relational embedding within and across organizational boundaries. This shows how coalitional politics shape and are shaped by the shifting boundaries of the firm, and how those politics affect the evolution of the production networks that prevail across many contemporary industries.